NUMERICAL SIMULATIONS OF TURBULENT GAS-SOLID FLOW IN A GRADUAL EXPANSION - Indiaryanto, Mahendra; Kusuma, Cahya; Arsad, Roy Mansyah (IJMEA Journal Kedokteran Gigi, 2024)
The dwindling availability of petroleum fuels encourages the use of fuel from renewable and environmentally friendly natural resources. This study focused on the iodine value in used biodiesel methyl ester and its effect on the performance of the main components of a diesel motor such as power, torque, brake mean effective pressure (BMEP), and specific fuel oil consumption (SFOC). Numerical research was carried out on the YANMAR TF85-MH engine model using computational fluid dynamics (CFD). The variations used are biodiesel B20, 20A, and 20B at three different engine rotation speeds, 1900 RPM, 2000 RPM, and 2100 RPM. The results show that the performance of biodiesel B20 is better compared to others. It produces 4.01 kW of power, 19.79 N.m of torque, 82065.12 Pa of BMEP, and 270.43 gr/Kwh of SFOC. While the B20A produces 4.61 kW of power, 20.44 N.m of torque, 84067.31 Pa of BMEP, and 288.76 gr/Kwh of SFOC. Then, the B20B produces 4.12 kW of power, 20.57 N.m of torque, 83244 Pa of BMEP, and 316.57 gr/Kwh of SFOC. So, it can be seen that the mixture of biodiesel fuel with iodine slightly affects the increase in diesel motor performance. In addition, the use of renewable energy fuels must be encouraged because their availability is maintained.